2020
DOI: 10.1111/ijfs.14692
|View full text |Cite
|
Sign up to set email alerts
|

Combination of freeze drying and molecular inclusion techniques improves the bioaccessibility of microencapsulated anthocyanins from black rice (Oryza sativa L.) and lavender (Lavandula angustifolia L.) essential oils in a model food system

Abstract: Black rice and lavender are promising sources of bioactives, in terms of anthocyanins and essential oils. Their bioaccessibility were improved by microencapsulation, followed by mixing in order to benefit both from colour and flavour, along with radical scavenging and biological properties. The mixed powder showed a satisfactory anthocyanins of 2.55 mg g −1 DW, leading to a radical scavenging activity of 65.14 mmol g −1 DW. The powder displayed an inhibitory effect against α-glucosidase (~49%) and α-amylase (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Similar results were reported by Kaderides et al (2020), who found that the cookies with encapsulated pomegranate peel extract retained about 90% from the initial antioxidant activity, whereas that of cookies with crude extract reached about 80% during storage for 21 days at 25 °C. The results are similar to Milea et al (2020), who reported an increase in biologically active compounds values during storage for 14 days of biscuits with microencapsulated anthocyanins from black rice and lavender essential oils. The microbiological test shown that the cookies were microbiologically satisfactory during the storage period (Tables 3 and 4).…”
Section: Storage Testsupporting
confidence: 90%
“…Similar results were reported by Kaderides et al (2020), who found that the cookies with encapsulated pomegranate peel extract retained about 90% from the initial antioxidant activity, whereas that of cookies with crude extract reached about 80% during storage for 21 days at 25 °C. The results are similar to Milea et al (2020), who reported an increase in biologically active compounds values during storage for 14 days of biscuits with microencapsulated anthocyanins from black rice and lavender essential oils. The microbiological test shown that the cookies were microbiologically satisfactory during the storage period (Tables 3 and 4).…”
Section: Storage Testsupporting
confidence: 90%
“…The anthocyanin content in black rice cultivars after germination was considerably higher than in red rice cultivars. Anthocyanin‐rich products have a brighter colour, improved nutritional and health profiles, and attract more consumers may contain pharmacological relevance and therapeutic applications (Carvalho et al ., 2016; Milea et al ., 2020); and may promote antiatherosclerosis, anticancer, antidiabetic, anti‐inflammatory and antitumor activities (Samyor et al ., 2017; Milea et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Pigmented rice genotypes have black, purple or red colour owing to the accumulation of natural pigments in the bran layer (Bhat & Riar, 2017; Melini & Acquistucci, 2017; Ma et al ., 2019). The anthocyanin present in pigmented rice has been reported to be the main source of phenolic compounds (Frank et al ., 2012; Milea et al ., 2020). Black rice contains anthocyanins, while red rice contains proanthocyanidins (PAs) (Gunaratne et al ., 2013; Hou et al ., 2013; Shao et al ., 2018; Rivero Meza et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…generating antioxidant activity and inhibition of α-amylase and α-glucosidase, with the aim of being released into the body for use in food. Milea et al [27] performed an extraction of anthocyanins in the essential oil of black rice and lavender and generated a microencapsulation of this with a mixture of soy protein isolate, soy protein hydrolysates and casein, which they lyophilized and obtained α-glucosidase inhibitory activity, radical scavenging and release in the intestine by in vitro assays. Other studies show the functionalization of carotenoids in different matrices.…”
Section: Food Colorants: Artificial Vs Naturalmentioning
confidence: 99%